Analisis Efektivitas Pembelajaran Daring pada mata Pelajaran Sejarah kelas XI IPS3 DI SMA N 5 Pariaman - Wike - Oktasix; Zafri Zafri (Jurnal Kronologi, 2021)
This research is motivated by the effectiveness of online learning during the COVID-19 pandemic in history subjects. The problems are 1) the COVID-19 pandemic has caused the Indonesian education system to change by following health protocols. 2) online learning is used as an option in conditions of the covid 19 pandemic. 3) with online learning many students cannot follow the lesson properly. 4) many students have difficulty in online learning. This study aims to determine the online learning process during covid 19 and to determine the effectiveness of online learning during the covid 19 pandemic. This type of research is quantitative using descriptive methods. The data sources in this study were obtained directly from information in the field through the distribution of questionnaires to 30 students. in class XI SMA N 5 Pariaman. The findings in this study indicate that the effectiveness of online learning is in the high category with a percentage of 90% with a distribution of 27 students and in the medium category the percentage of 10% with a distribution of 3 students. The results of the research in general, the effectiveness of online learning components show components of online learning preparation with a high category at a percentage of 63%, components of implementing online learning in a high category at a percentage of 63% and an online learning assessment component with a high category at a percentage of 61%. Keywords: Effectiveness of online learning, online learning components. Abstrak Penelitian ini dilatar belakangi oleh efektivitas pembelajaran secara daring selama masa pandemi covid 19 pada mata pelajaran sejarah. Permasalahannya 1) kondisi pandemi covid 19 menyebabkan sistem pendidikan Indonesia berubah dengan mengikuti protokol kesehatan. 2) pembelajaran secara daring digunakan sebagai pilihan dalam kondisi pandemi covid 19. 3) dengan pembelajaran daring banyak peserta didik tidak dapat mengikuti pembelajaran dengan baik. 4) banyaknya peserta didik mendapatkan kesulitan dalam pembelajaran daring. penelitian ini bertujuan untuk mengetahui proses pembelajaran daring selama covid 19 dan untuk mengetahui keefektifan pembelajaran daring pada masa pandemi covid 19. Jenis penelitian ini ialah kuantitatif dengan menggunakan metode deskrptif sumber data dalam penelitian ini diperoleh secara langsung dari informasi dilapangan melalui penyebaran angket kepada 30 peserta didik di kelas XI SMA N 5 Pariaman. Temuan dalam penelitian ini menunjukkan bahwa efektivas pembelajaran daring berada pada kategori tinggi persentase 90% dengan sebaran 27 peserta didik dan pada kategori sedang persentase 10% dengan sebaran 3 peserta didik. Hasil penelitian secara umum efektivitas pembelajaran daring perkomponen menunjukkan komponen persiapan pembelajaran daring dengan kategori tinggi pada persentase 63 %, komponen pelaksanaan pembelajaran daring dengan kategori tinggi pada persentase 63 % dan komponen penilaian pembelajaran daring dengan kategori tinggi pada persentase 61 %. Kata kunci : Efektivitas pembelajaran daring, Komponen pembelajaran secara daring.